Eupatilin attenuates the senescence of nucleus pulposus cells and mitigates intervertebral disc degeneration via inhibition of the MAPK/NF-κB signaling pathway - Yang, Huan; Yang, Xiao; Rong, Kewei; Liang, Jiarong; Wang, Zhengting; Zhao, Jie; Zhang, Pu; Li, Yijie; Wang, Lihuan; Ma, Hui; Ye, Bin (Frontiers in Pharmacology, 2022)
Intervertebral disc degeneration (IDD) is the main cause of low back pain. An increasing number of studies have suggested that inflammatory response or the senescence of nucleus pulposus (NP) cells are strongly associated with the progress of IDD. Eupatilin, the main flavonoid extracted from Artemisia, was reported to be associated with the inhibition of intracellular inflammatory response and the senescence of cells. However, the relationship between Eupatilin and IDD is still unknown. In this study, we explored the role of Eupatilin in tumor necrosis factor-α (TNF-α)-induced activation of inflammatory signaling pathways and NP cell senescence, in the anabolism and catabolism of NP cells extracellular matrix (ECM), and in the effect of puncture-induced model of caudal IDD in rat. In vitro, Eupatilin significantly inhibited TNF-α-induced ECM degradation, downregulated the expression of related markers of NP cells (MMP3, MMP9 and MMP13), and upregulated the expression of SOX9 and COL2A1. Furthermore, Eupatilin reduced TNF-α-induced cell senescence by inhibiting the expression of the senescence of NP cells related markers (p21 and p53). Mechanistically, ECM degradation and cell senescence was reduced by Eupatilin inhibited the activation of MAPK/NF-κB signaling pathways. Consistent with the in vitro data, Eupatilin administration ameliorated puncture-induced model of caudal IDD in rat. In conclusion, Eupatilin can inhibit the inflammatory response and the senescence of NP cells, which may be a novel treatment strategy for IDD.